Mindfulness in Basic Education: A Systematic Review Enhancing Learning Focus (2021–2026) - Asifa Adilya Hanuza; A. Fatoni; Muhammad Muchsin Afriyadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study conducted a systematic review to examine the role of self-awareness in increasing learning focus and its contribution to strengthening student independence in elementary school. A total of 12 scientific articles published in the 2021–2026 range were comprehensively analyzed. The results of the study show three main mechanisms that make self-awareness-based mindfulness a key intervention. First, self-awareness plays a role in improving the executive function of the brain, including attention control, inhibition of impulsive responses, and cognitive flexibility, which are neurocognitive prerequisites for learning focus. Second, self-awareness provides practical strategies for managing anxiety and stress that can interfere with concentration, while also improving students' emotional awareness. Third, self-awareness supports the formation of school culture and teacher practices that create a supportive learning ecosystem. Advanced synthesis analysis showed that the reinforcement of self-control acted as a mediator explaining the indirect relationship between self-awareness and increased learning focus. Based on these findings, this study recommends the systematic integration of self-awareness practices through reflective activities, simple mindfulness exercises, and emotionally responsive learning strategies in the curriculum and training of elementary school teachers to support academic development, especially in improving learning focus.